Condition Based Monitoring For Protection System - Ahmad Aliff Irwan Bin Zakaria, Ahmad Aliff (2010)
The objective of this project is to implement Condition Based Monitoring into Power System Protection. This project is focusing on the distribution level protection system with 11kV voltage rating.